Total Hip Replacement in Chronic Slipped Capital Femoral Epiphysis with Degenerative Joint Disease: A Case Report - Tjahjadi, Berlianto; Dwiputra H., Kukuh; M D S, Jifaldi Afrian; Chilmi, M. Zaim (The Hip and Knee Journal, 2023)
Slipped capital femoral epiphysis (SCFE) is the most common hip disorder affecting the adolescent population, with a reported annual incidence of 8.8 to 10.8 per 100,000 children aged 9 to 16 years. SCFE is known to affect boys more often than girls. Chondrolysis and osteonecrosis of the hip can accelerate hip degeneration related to SCFE, leading to end-stage hip disease. Total Hip Arthroplasty (THA) is the primary treatment option for managing end-stage hip Osteoarthritis (OA) in SCFE patients. A 22 years old male presented with a 2,5 years of pain in the left hip joint with a history of trauma three years ago; after that, he could still walk. Four months later, he feels pain in the left hip that gets aggravated on walking and cannot walk for long distances (5-10m). Postoperatively the patient has an equal leg length, with less pain on the hip with a good range of motion, and can walk dependently using a cane. THA to be a feasible treatment option in young patients with secondary osteoarthritis of the hip due to SCFE. Uncemented THA has a good survivorship rate.